12 Weeks of Combined Endurance and Resistance Training Reduces Innate Markers of Inflammation in a Randomized Controlled Clinical Trial in Patients with Multiple Sclerosis. (20th January 2016) - Deckx, Nathalie; Wens, Inez; Nuyts, Amber H.; Hens, Niel; De Winter, Benedicte Y.; Koppen, Gudrun; Goossens, Herman; Van Damme, Pierre; Berneman, Zwi N.; Eijnde, Bert O.; Cools, Nathalie
Abstract : Previously, we reported that patients with multiple sclerosis (MS) demonstrate improved muscle strength, exercise tolerance, and lean tissue mass following a combined endurance and resistance exercise program. However, the effect of exercise on the underlying disease pathogenesis remains elusive. Since recent evidence supports a crucial role of dendritic cells (DC) in the pathogenesis of MS, we investigated the effect of a 12-week combined exercise program in MS patients on the number and function of DC. We demonstrate an increased number of plasmacytoid DC (pDC) following the exercise program. These pDC display an activated phenotype, as evidenced by increased numbers of circulating CD62L + and CD80 + pDC. Interestingly, the number of CD80 + pDC positively correlates with the presence of IL-10-producing regulatory type 1 cells (Tr1), an important cell type for maintaining peripheral tolerance to self-antigens. In addition, decreased production of the inflammatory mediators, TNF- α and MMP-9, upon Toll-like receptor (TLR) stimulation was found at the end of the exercise program. Overall, our findings suggest that the 12-week exercise program reduces the secretion of inflammatory mediators upon TLR stimulation and promotes the immunoregulatory function of circulating pDC, suggestive for a favorable impact of exercise on the underlying immunopathogenesis of MS.